(untitled) (Contemporary Mathematics, 2025)
The target of this paper is to discuss a new subclass of schlicht mappings with negative coefficients correlated to Erdely-Kober Integral Operator in the unit disk U = w ∈ C : |w| < 1. For mappings in our class, we learn fundamental properties like the Hadamard product, the coefficient inequality, the distortion and covering theorem, the radii of starshapeness, the convexity and close-to-convexity, the extreme points, and the closure theorems.